Batman. The long Halloween. Part two [videorecording (Blu-Ray)] - Loeb, Jeph (Warner Bros. Home Entertainment, 2021)
The Dark Knight races the clock, and the calendar, to uncover the mystery of the Holiday killer stalking Gotham's criminal underground. But when a close ally falls, a new threat emerges to give the fight a terrifying new face.